The Heritability of ADHD in Children of ADHD Parents: A Post-hoc Analysis of Longitudinal Data. Issue 3 (February 2023) - Uchida, Mai; DiSalvo, Maura; Walsh, Daniel; Biederman, Joseph
Objective: A growing literature suggests attention-deficit/hyperactivity disorder (ADHD) is a heritable disorder. We evaluated children at risk for ADHD by virtue of having parents with ADHD and compared them with children of parents without ADHD to assess the degree of heritability of ADHD. Method: The sample for this study was derived from three longitudinal studies that tracked families with various disorders, including ADHD. Children were stratified based on presence of parental ADHD, and clinical assessments were taken to evaluate presence of ADHD and related psychiatric and functional outcomes in children. Results: Children with parental ADHD had significantly more full or subthreshold psychiatric disorders (including ADHD) as well as functional impairments compared to children without parental ADHD. Conclusion: Our findings suggest that offspring of parents with ADHD are at significant risk for ADHD and its associated psychiatric, cognitive, and educational impairments. These findings aid in identifying early manifestations of ADHD in young children at risk.